Influence of the microstructure on the corrosion behaviour of 2024 aluminium alloy coated with a trivalent chromium conversion layer. (September 2018) - Saillard, R.; Viguier, B.; Odemer, G.; Pugliara, A.; Fori, B.; Blanc, C.
Graphical abstract: Highlights: Nanometer scale Cu-rich precipitates behaved as distinct electrochemical entities. They contributed to the surface Cu coverage of the deoxidised alloy. The surface Cu coverage was increased for long-aged samples. Thicker but more defective TCP coatings formed on long-aged samples. TCP coatings formed on long-aged samples had low protective properties. Abstract: The influence of 2024 aluminium alloy microstructure on the protective properties of trivalent chromium process (TCP) coatings was studied: samples aged at 190 °C were analysed by comparison to a T3 state. The surface Cu coverage after deoxidation was higher for long-aged samples because nanometer scale Cu-rich precipitates formed during ageing behaved as distinct electrochemical entities and contributed to the formation of copper deposits. The growth mechanisms and kinetics of TCP coatings were directly related to the surface Cu coverage: thicker but more defective TCP coatings formed on long-aged samples leading to the lowest anti-corrosion properties.